2020
DOI: 10.1186/s12889-020-09526-3
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ knowledge, attitude and practice towards children’s vaccination in Lebanon: role of the parent-physician communication

Abstract: Background One of the most effective public health interventions in the world is immunization. However, some parents doubt its usefulness and safety. Many factors influence their decision to vaccinate, including their sociodemographic characteristics, their trust in the public health system, the parent-physician relationship, their level of knowledge and their attitudes towards vaccination. Our objective was to determine the factors, especially the parent-physician communication, associated with parental knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 42 publications
(61 reference statements)
10
32
2
Order By: Relevance
“…Our study showed that respondents who had good knowledge about infant immunization were four folds (AOR= 4.592, 95% CI: (2.709–7.786) more likely to had a favorable attitude towards infant immunization than their counterparts. This is in line with studies conducted in Saudi Arabia, 25 , 26 Bangalore, India, 46 Lebanon, 49 Lithuania, 34 and Italy. 55 This might be due to good knowledge was the most crucial and tangible factor that helps to attain a favorable attitude towards infant immunization and mothers who had better knowledge and understanding about EPI were more likely to adhere and less likely to refuse their infant’s immunization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study showed that respondents who had good knowledge about infant immunization were four folds (AOR= 4.592, 95% CI: (2.709–7.786) more likely to had a favorable attitude towards infant immunization than their counterparts. This is in line with studies conducted in Saudi Arabia, 25 , 26 Bangalore, India, 46 Lebanon, 49 Lithuania, 34 and Italy. 55 This might be due to good knowledge was the most crucial and tangible factor that helps to attain a favorable attitude towards infant immunization and mothers who had better knowledge and understanding about EPI were more likely to adhere and less likely to refuse their infant’s immunization.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that Literate parents who attend higher education were about five times (AOR=5.330, 95% CI: (1.919-14.803)) more likely to be knowledgeable than illiterate respondents. This finding is comparable with the study findings from Addis Ababa, 40 Minia City, Egypt, 36 Nigeria, 39,44 Saudi Arabia, 17,18,25 Nepal, 32 India, 28,47,48 Lebanon 49 and Lithuania. 34 This was due to higher educational levels, of no doubt, have a good understanding of children's health and understand the educational messages and vaccination policy much more easily.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The role of education was notable because education mostly correlates with positive attitudes and behavior toward vaccination [76][77][78]. The opposite, as in the case of this study, is not frequently found.…”
Section: Discussionmentioning
confidence: 44%
“…To be successful, vaccination programs rely on a high uptake level. It is estimated that less than 5-10% of individuals have strong anti-vaccination attitudes (18). However, a more significant proportion could be categorized as being hesitant regarding vaccination.…”
Section: Discussionmentioning
confidence: 99%